Low-Energy Electron Induced Reactions in Metronidazole at Different Solvation Conditions - Christine Lochmann; Thomas F. M. Luxford; Samanta Makurat; Andriy Pysanenko; Jaroslav Kočišek; Janusz Rak; Stephan Denifl (MDPI AG, 2022)
Metronidazole belongs to the class of nitroimidazole molecules and has been considered as a potential radiosensitizer for radiation therapy. During the irradiation of biological tissue, secondary electrons are released that may interact with molecules of the surrounding environment. Here, we present a study of electron attachment to metronidazole that aims to investigate possible reactions in the molecule upon anion formation. Another purpose is to elucidate the effect of microhydration on electron-induced reactions in metronidazole. We use two crossed electron/molecular beam devices with the mass-spectrometric analysis of formed anions. The experiments are supported by quantum chemical calculations on thermodynamic properties such as electron affinities and thresholds of anion formation. For the single molecule, as well as the microhydrated condition, we observe the parent radical anion as the most abundant product anion upon electron attachment. A variety of fragment anions are observed for the isolated molecule, with NO2− as the most abundant fragment species. NO2− and all other fragment anions except weakly abundant OH− are quenched upon microhydration. The relative abundances suggest the parent radical anion of metronidazole as a biologically relevant species after the physicochemical stage of radiation damage. We also conclude from the present results that metronidazole is highly susceptible to low-energy electrons.